Connectedness via Generalizations of Semi-Open Sets - J. Mahmood, Ali; A.I., Naser (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
We use the idea of the grill. This study generalized a new sort of linked space like -connected and -hyperconnected and investigated its features, as well as the relationship between it and previously described notions. It also developed new sorts of functions, such as hyperconnected space, and identified their relationship by offering numerous instances and attributes that belong to this set. This set will serve as a starting point for further research into the set many future possibilities. We also use some theorems and observations previously studied and related to the grill and the semi-open to obtain results in this research. We applied the concept of connected to them and obtained results related to connected. The sources related to the connected and semi-open where considered as starting points and an important basis in this research.